Posterior cerebral artery (PCA) infarcts and dreaming : a neuropsychological study - Marchbank, Gavin Clyde (Department of Psychology, 2015)
Recent case reports have shown that global loss of dreaming can result from medial occipitotemporal lesions. These findings have cast doubt on Solms's reformulation of Charcot-Wilbrand Syndrome (CWS) into two distinct disorders of dreaming, and caused substantial confusion in dream research as far as the neurological correlates of dreaming are concerned. This study attempted to confirm these case reports and determine whether there were any characteristics unique to the lesions among patients who had lost the ability to dream following damage to medial occipito-temporal cortex. Nine participants (three non-dreamers and six dreamers) who had suffered non-hemorrhagic infarction in the territory of the posterior cerebral artery were recruited in this study. Case histories and neuroradiological data were used to compare the lesion sites of non-dreamers with dreamers. It was confirmed that complete loss of dreaming could result from lesions in medial occipito-temporal cortex. It was found that non-dreamers always suffered bilateral cortical damage as opposed to dreamers who all suffered unilateral damage. The lesions in the non-dreamers tended to be more posterior than the dreamers. It was further speculated that concomitant damage to the thalamus or parietal areas played a role in the causation of heteromodal loss of dreaming. The implications of these findings were discussed in relation to CWS, Solms's dream system, and dream-function research. Finally, future directions were considered.